PENGARUH PROFITABILITY TERHADAP MARKET CAPITALIZATION PERBANKAN KONVENSIONAL (2012-2021) - Dhea Prisma Shelawangi; Marlinda Nur Aisyah; Fathur Rozi Farori; Vira Yulita Kurniawati (Nusantara Hasana Journal, 2023)
This study aims to determine whether the profitability ratios can affect the value of market capitalization. So the researchers drew the title "Profitability Influence on conventional banking market capitalization (2012-2021). The independent variable of this research is ROE ROA ROI while the dependent variable is the value of market capitalization. This study used a quantitative method with sampling using a purposive sampling method so that 10 banks that met the criteria were obtained. The tests were carried out using Eviews 10. The results of this study show that simultaneously ROE ROA and ROI have a simultaneous effect on the value of market capitalization using the f test. while the t test shows that ROA partially affects market capitalization. In the t-test, ROI has no effect on market capitalization. Meanwhile, ROE has a partial effect on market capitalization.